Review on photonic crystal fibers with hybrid guiding mechanisms - Hu, Dora Juan Juan (2019)
Photonic crystal fibers (PCFs) with hybrid guiding mechanisms have undergone substantial development in recent years. Due to the co-existence of index-guiding and photonic bandgap (PBG)-guiding mechanisms in this special class of PCFs, many peculiar properties have been investigated and demonstrated as advantageous and favorable in many applications. This review paper provides a comprehensive review of the recent progress of these hybrid guiding PCFs. The first part explains the principles of the hybrid guiding mechanisms in the PCF structures. The hybrid guiding PCFs are realized in three approaches, including polarization-dependent hybrid guiding PCFs, radial hybrid guiding PCFs, and two-core hybrid guiding PCFs. This is followed by a review of various development and applications for each type of hybrid guiding PCFs in the second part, including tunable filters, high power lasers, nonlinear optics, and polarization optics and sensing applications. Finally, the considerations and challenges on the potential applications of the hybrid guiding PCFs are discussed.